In cats with cranial cruciate rupture are better long-term outcomes achieved by surgical or conservative management? - Montgomery, Philip (Veterinary Evidence, 2025)
Question In cats diagnosed with isolated rupture of the cranial cruciate ligament, does surgical intervention result in improved long-term function, when compared with conservative management? Clinical bottom line The category of research question was: Treatment. The number and type of study designs that were critically appraised were: One retrospective cohort study comparing surgical management and conservative management. Critical appraisal of the selected papers meeting the inclusion criteria collectively provide zero/weak/moderate/strong evidence in terms of their experimental design and implementation: Weak. The outcomes reported are summarised as follows… This study evaluated and compared the long-term Feline Musculoskeletal Pain Index (FMPI) of patients with a cranial cruciate injury (39–87 months post injury). Patients that were managed conservatively showed statistically significant (P = 0.017) lower FMPI scores long term. In view of the strength of evidence and the outcomes from the studies the following conclusion is made… Conservative management can be considered in cats presenting with isolated cranial cruciate rupture; however, further research is required to establish the optimum treatment in these cases. Given the limitations of this study and the current lack of evidence, clinicians must rely on their clinical judgement at this point when managing this condition until further research is available.